2012
DOI: 10.1177/1329878x1214400115
|View full text |Cite
|
Sign up to set email alerts
|

Talking in a Crowded Room: Political Blogging during the 2008 New Zealand General Election

Abstract: This article analyses two of New Zealand's foremost political blogs on public affairs in the four weeks prior to the 2008 New Zealand general election. The 2008 election represents, we argue, a moment when the scale and reach of blogging propelled it to a position of significance in New Zealand media. The study uses content analysis to track the material posted on these blogs and in their comments sections. It is concerned primarily with quantifying the kind of debate to be found there and, through that, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The predictive accuracy for this part was a low MAD of 0.44%, suggesting the methodology was successful in representing the electorates, although our sample had only a few (n = 6) favoring this party. In New Zealand, the official election campaigning commences 4 weeks prior to Election Day (Hopkins & Matheson, 2012). In the 4 weeks of campaigning the party standing alters as the party candidates "drip-feed" their manifesto elements through the media channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive accuracy for this part was a low MAD of 0.44%, suggesting the methodology was successful in representing the electorates, although our sample had only a few (n = 6) favoring this party. In New Zealand, the official election campaigning commences 4 weeks prior to Election Day (Hopkins & Matheson, 2012). In the 4 weeks of campaigning the party standing alters as the party candidates "drip-feed" their manifesto elements through the media channels.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, the official election campaigning commences 4 weeks prior to Election Day (Hopkins & Matheson, 2012). In the 4 weeks of campaigning the party standing alters as the party candidates “drip-feed” their manifesto elements through the media channels.…”
Section: Discussionmentioning
confidence: 99%
“…That is, they often link to and discuss ''sites with opposing views to highlight alternative, or possibly 'wrong', interpretations of issues'' (p. 92). 6 Furthermore, while researchers in the U.S. and New Zealand (Hopkins and Matheson, 2012) found that political blogs may often have partisan interests-such as supporting specific political candidates or political parties-this is not always the case in the Australia political blogosphere. Certainly Australian political blogs often array themselves on the left or right of the political spectrum, but this does not necessarily translate into the support of any particular politicians.…”
Section: Political Blogging and Deliberative Exchangesmentioning
confidence: 98%
“…What had changed from the 2005 election to the 2008 election for Hopkins and Matheson (2012) was not the blogs or bloggers themselves, as they retained largely the same characteristics across the elections (and in fact many of the same individual bloggers), but rather they found that the levels of debate in the comments sections had increased markedly.…”
Section: Political Blogging In New Zealandmentioning
confidence: 99%
“…115-116), and that part of the attraction appeared to be due to the debate being more "direct, less mediated, and more intense" (p. 116). However, Hopkins and Matheson (2012) did conclude that, despite this, those who participated were quite resolutely partisan, and the ideals of a multiplicity of perspectives being discussed were "not well realised in the New Zealand political blogosphere" (p. 116).…”
Section: Political Blogging In New Zealandmentioning
confidence: 99%